The Effect of Quality of Work-Life on The Desire to Settle With Organizational Commitment As an Intervening Variable at The Kudus Aisyiyah Hospital - Prastyo, Agus; Nuryakin, N; Aini, Qurrotul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
This is an explanatory study that examines the impact of work-life quality on the desire to settle using organizational commitment as an intervening variable in Aisyiyah Kudus Research Hospital. The major data source consists of providing direct questionnaires to 145 respondents who work with RS Aisyiyah Kudus. Path Analysis is a method for analyzing data. According to the findings of this study's analysis, (1) there is a positive and significant influence of organizational commitment on the quality of work-life in the Aisyiyah Kudus Hospital; (2) there is a positive and significant influence of organizational commitment on the desire to settle in the Aisyiyah Kudus Hospital; (3) there is a positive and significant influence on organizational commitment on the desire to settle in the Aisyiyah Kudus Hospital; and (4) there is a positive and significant influence on the desire to settle in the Aisyiyah Kudus Hospital on the quality of work-life (5) The mediation of organizational commitments at the Aisyiyah Kudus Hospital has a favourable and significant impact on the quality of work-life and the desire to settle down.